Morphogenic and structural characteristics of tropical forage grasses managed under different regrowth periods in the Brazilian semi-arid region - Genildo Fonseca Pereira; João Virgínio Emerenciano Neto; Gelson dos Santos Difante; Liz Carolina da Silva Lagos Cortes Assis; Patrícia de Oliveira Lima (Semina: Ciências Agrárias, 2019)
The objective of this study was to evaluate the morphogenetic and structural characteristics of tropical grasses managed under different regrowth periods. The experiment was conducted at the Federal Institute of Science and Technology Education of Rio Grande do Norte, located in the municipality of Apodi-RN, Brazil. The study design was in randomized blocks and the treatments were allocated in a 3x4 factorial arrangement, with three cultivars (Andropogon, Buffel and Massai) in four regrowth periods (21, 35, 49 and 63 days). The interaction between cultivar and age was significant for all studied variables, with the exception of leaf blade width and accumulation rate. The highest leaf appearance rates were observed in Buffel grass, regardless of the regrowth age. This characteristic was not influenced by age only in Andropogon grass. Higher stem elongation rates were observed in Buffel grass, while the lowest were observed in Massai grass until 35 days of regrowth, attributed to the presence of inflorescences. Canopy heights in Massai and Andropogon grass were greater than Buffel grass until 35 days of regrowth, Andropogon grass had higher height from 35 days of regrowth than the others. Andropogon grass showed higher rates of accumulation than Massai grass only at 21 days of regrowth, and no effects of regrowth age were observed for this variable. Buffel grass should be defoliated at 21 days, while Andropogon and Massai grass can be managed without losses between 21 and 63 days of regrowth.